Media Reports and Knowledge of e-Cigarette or Vaping Use-Associated Lung Injury Among Adolescents in California: Population-Based Cross-Sectional Study - Jijiang Wang; John Ayers; Eric Leas; Anthony Gamst; Shu-Hong Zhu (Journal of Medical Internet Research)
Abstract Backgrounde-Cigarette or vaping use-associated lung injury (EVALI), first reported in July 2019, caused over 2807 hospitalizations and 68 deaths by February 2020, when the outbreak subsided and the Centers for Disease Control and Prevention (CDC) stopped updating the case number. Media coverage of EVALI was extensive but not always accurate concerning the cause, which turned out to be vitamin E acetate, a compound added to certain illicit cannabis vape products. Studies have documented a significant increase in the perceived risk of vaping among the US adult population. However, research on how the EVALI outbreak influenced adolescents’ knowledge of the illness and their perception of the risk of vaping products is limited, especially those that used probability sampling of the adolescent population. ObjectiveThis study examined knowledge of EVALI among adolescents and explored the impact of media messages on their perceptions of the condition. MethodsArchived news reports on EVALI from an online tobacco media analysis engine, Tobacco Watcher (July 2019-March 2020), and data from the California Student Tobacco Survey, a large statewide school-based survey of 8th, 10th, and 12th graders (September 2019–March 2020; N=157,499), were analyzed. Students’ awareness of EVALI and perceptions of its cause were examined in relation to their sources of information about EVALI, and their perceived risk of vaping was analyzed by their awareness of EVALI. ResultsOf 19,661 news reports on Tobacco Watcher that discussed EVALI, 55.9% mentioned cannabis. Among the 157,499 middle and high school students participating in the statewide survey in California, 75% had heard about EVALI. The awareness level was similarly high for 8th, 10th, and 12th graders (75.7%, 74.6%, and 74.8%, respectively). Their primary source of knowledge about EVALI was media (63.1%), followed by parents (16.6%), teachers (8.1%), friends (7.7%), and peers (4.6%). Most students, 55%, believed nicotine was the cause of EVALI, while only 11% thought it was related to cannabis in vapes. Students who had heard about EVALI were more likely to rate vaping every day as extremely harmful than those who had not heard about it (67.8% vs 50.9%; P ConclusionsMost adolescents were aware of EVALI and cited media as the main source of their knowledge. The effects of extensive news coverage of EVALI have reached students as young as 8th graders. Most of those who were aware of EVALI, however, incorrectly believed that nicotine in vapes was the cause of EVALI. The actual cause—vitamin E acetate found in certain cannabis vapes—appeared to have been overlooked or not effectively communicated, especially in early media reports. Media coverage of EVALI presents a case study of the critical but complicated role of modern media in communicating health information.